Menggantung ke “Atas”: Perkumpulan Sosial Perdesaan di Era Desentralisasi - Mahendro, Anggoro Yudo (Masyarakat: Jurnal Sosiologi, 2013)
In democracy, the government at the national and local level strives to create an active community, which manifests in a variety of community associations. Desa Rintis shows the active role of local government in supporting the establishment of community associations at the village level. We can understand this because the local government has the structural strength through its regulations to influence the society. Besides, the local government also provides cultural as well as economic capital that is included in the relational process between the state and social associations. This condition causes initiative of some members of the community to form associations and engage in social activities. Judging from the concept of social capital, social associations in the Desa Rintis have social capital that is not balanced between bonding, bridging, and linking. Social associations are strong on the linking side, however, they are weak on the bonding and bridging side. Therefore, the existence of social associations in the village Rintis just hangs up (to the state). Said to hang because of the active efforts from the leaders of the social associations to involve themselves with the state. This condition is the feedback from the top-down pattern that was developed earlier by the state.